Passionate Leadership : Creating a Culture of Success in Every School. - Thomas-EL, Salome (SAGE Publications, 2019)
Reignite your passion for serving children! This is an inspiring call to action for teachers and principals around the world to recommit to passionately serving children, building the communities children deserve, and celebrating our successes. The authors of this book examine what it takes to be a passionate leader and take courageous actions which lead to student growth and success. Educators ready to push to new heights and break boundaries will find: Practical ideas and suggestions for how to serve as a beacon of hope in the field First-hand experiences from enthusiastic leaders modeling.